16th seduction - Patterson, James, 1947-; Paetro, Maxine (New York : Little, Brown and Company, 2017)
Fifteen months ago Detective Lindsay Boxer's life was perfect - she had a beautiful child and a doting husband, Joe, who helped her catch a ruthless criminal who'd detonated a bomb in downtown San Francisco, killing 12 people. But Joe isn't everything that Lindsay thought he was, and she's still reeling from his betrayal as a wave of mysterious and possibly unnatural heart attacks strikes seemingly unrelated victims across San Francisco. Now the bomber she and Joe captured is about to go on trial, and his defense raises damning questions about Lindsay and Joe's investigation. Not knowing whom to trust, and struggling to accept the truth about the man she thought she knew, Lindsay must connect the dots of a deadly conspiracy before a brilliant criminal puts her on trial.
Keywords: Boxer, Lindsay -- (Fictitious character) -- Fiction; Women's Murder Club (Imaginary organization) -- Fiction; Policewomen -- California -- San Francisco -- Fiction; Murder -- Investigation -- Fiction; San Francisco (Calif.) -- Fiction; Thrillers (Fiction); Detective and mystery fiction